2018
DOI: 10.1186/s13063-018-2620-9
|View full text |Cite
|
Sign up to set email alerts
|

Individualized, perioperative, hemodynamic goal-directed therapy in major abdominal surgery (iPEGASUS trial): study protocol for a randomized controlled trial

Abstract: BackgroundPostoperative morbidity and mortality in patients undergoing surgery is high, especially in patients who are at risk of complications and undergoing major surgery. We hypothesize that perioperative, algorithm-driven, hemodynamic therapy based on individualized fluid status and cardiac output optimization is able to reduce mortality and postoperative moderate and severe complications as a major determinant of the patients’ postoperative quality of life, as well as health care costs.Methods/designThis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Thus, we deliberately chose the semi-invasive pulse-contour analysis method as a reference. Alternative semi-invasive devices for non-calibrated pulse-contour analysis-based CO measurement are currently under investigation in the context of perioperative, individualized hemodynamic optimization in a large, international randomized controlled study [48]. A further limitation may be that the ipsilateral measurement of intra-arterial pressure from the reference radial line likely introduced bias for the finger cuff photopletysmography based measurements of the small finger arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we deliberately chose the semi-invasive pulse-contour analysis method as a reference. Alternative semi-invasive devices for non-calibrated pulse-contour analysis-based CO measurement are currently under investigation in the context of perioperative, individualized hemodynamic optimization in a large, international randomized controlled study [48]. A further limitation may be that the ipsilateral measurement of intra-arterial pressure from the reference radial line likely introduced bias for the finger cuff photopletysmography based measurements of the small finger arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Won et al reported that using SPI monitoring during general anesthesia reduced opioid consumption, improved hemodynamic stability, and reduced postoperative recovery times [ 71 ]. A similar study was carried out by Jain et al, which showed a statistically significant decrease in the number of hemodynamic adverse events when SPI was used for the titration of opioid medication ( p < 0.05) [ 70 ].…”
Section: Monitoring Techniques For the Nociception-antinociceptionmentioning
confidence: 74%
“…Numerous studies have shown that opioid overdose during anesthesia is responsible for a series of adverse effects, such as increased recovery times and opioid induced hyperalgesia, and that opioid overdose also leads to hypotension, having a major impact on perioperative hemodynamic stability [ 66 , 67 , 68 , 69 , 70 , 71 ]. Won et al reported that using SPI monitoring during general anesthesia reduced opioid consumption, improved hemodynamic stability, and reduced postoperative recovery times [ 71 ].…”
Section: Monitoring Techniques For the Nociception-antinociceptionmentioning
confidence: 99%
“…[ 5 ] They depicted a significantly decreased rate of postoperative complications. However, the individualized perioperative hemodynamic goal-directed therapy in major abdominal surgery (iPEGASUS) trial outlined a comparable complication rate following the GDT protocol of an individually optimized CO.[ 6 ] Ackland et al . emphasized the significance of an individualized oxygen delivery targeted hemodynamic management at alleviating postoperative morbidity following high-risk surgery.…”
mentioning
confidence: 99%